Long-term effects of dalfampridine in patients with multiple sclerosis - Ruck, T.; Bittner, S.; Simon, O.J.; Göbel, K.; Wiendl, H.; Schilling, M.; Meuth, S.G. (Journal of the neurological sciences, 2014)
Dalfampridine is the extended-release formulation of 4-aminopyridine and is approved for the symptomatic treatment of impaired mobility in patients with multiple sclerosis. Our aim was to examine the short- and long-term effects of treatment with dalfampridine on motoric and cognitive assessment parameters of multiple sclerosis (MS) patients over 9–12months. Fifty-two patients with MS with an EDSS between 4.0 and 7.0 and impaired mobility were evaluated for parameters of walking ability, MSFC, cognitive and motor fatigue and evoked potentials at treatment initiation with dalfampridine as well as 2weeks and after 9–12months later. Thirty out of fifty-two patients (~60%) were still on treatment after 9–12months. Two weeks after treatment initiation, significant ameliorations could be found for T25FW, maximum walking distance as well as motoric and cognitive fatigue which still persisted after 9–12months. In contrast significant effects for velocity were observed only after 2weeks, for improvement in PASAT only after 9–12months. A tendency for improvement of somatosensory evoked potentials was found in a subset of patients. Dalfampridine shows positive short- and long-term effects on motoric and cognitive assessment parameters in an open-label observational study in a cohort of patients with MS.